The time interval between ovarian stimulation with FSH/LH and ovum-pick up affects the quantity, quality and developmental competence of oocytes retrieved from Ecuadorian creole heifers - Ayala Guanga, Luis (2020)
The aim of this study was to evaluate the effects of gonadotropin treatment and the interval between ovarian stimulation with FSH/LH and the follicular aspiration session, on the quantity and quality of the cumulus oocyte complexes (COCs) obtained by ovum pick up (OPU) ) in Ecuadorian Creole heifers. Four heifers were randomly assigned to four groups (FHS/LH 40h; FSH/LH 48h; control 40h; control 48h). In two groups a dose (0.011 mg, IM) of GnRH was applied on day 0, followed by 500 IU, IM, of FSH/LH on day 2, and the OPU session at 40 (FSH/LH 40 h) or 48 hours (FSH/LH 48h) after the application of gonadotropin. In the other two groups, FSH/LH was replaced by a physiological solution. There was no statistical difference in the recovery rate of COCs between FSH/LH 40h and FSH/LH 48h, but approximately twice as many COCs (p<0.05) were obtained than in those who did not receive ovarian stimulation. In addition, 2.4 times more COCs of quality A were achieved in the treatment of FSH/LH 48h than in that of FSH/LH 40h. All (100%) of these structures reacted positively to Brilliant Cresyl Blue (BCB+), which means that they finished the growth and were competent to initiate in vitro maturation. It is concluded that the treatment with FSH/LH 48h allowed to obtain a greater number of COCs competent for in vitro maturation.